'We're physicists': Gender, genre and the image of scientists in The Big Bang Theory. Issue 1 (1st April 2015) - Weitekamp, Margaret A.
As a comedy, the popular CBS television show The Big Bang Theory (2007–) has made an international commercial success of its portrayal of scientists, complete with equation-laden white boards and an affectionate depiction of nerd culture. Working both with and against the gendered stereotypes of the nerd and the mad scientist – and drawing upon many of the core characteristics of situation comedy as a genre – The Big Bang Theory offers a sympathetic and nuanced depiction of scientists, including a more diverse group of scientists by gender, ethnicity, and scientific subfields than usually seen in either television or movies.